PENGARUH MENGGAMBAR BEBAS TERHADAP KREATIVITAS ANAK USIA DINI KELOMPOK B DI TA AL KAUTSAR KOTA MALANG - Hadijah Hadijah; Ika Anggraheni; Ari Kusuma Sulyandari (UNISMA, 2022)
This study entitled The Effect of Free Drawing on Early Childhood Creativity in Group B in TA Al Kautsar Malang City. The background of this research is about teaching children to draw freely according to their ability and imagination to express ideas and channel their feelings through pictures and creativity. This study uses several stationery as well as by coloring pictures according to the needs of each child. Development data were obtained through questionnaires in TA Al Kautsar Malang City and from various instrument test results through questionnaire data with the help of students' parents. So the results of this study were obtained through the parents of students by filling out the questionnaire.